Resolution dependence of interlinked Southern Ocean biases in global coupled HadGEM3 models - D. Storkey; P. Mathiot; M. J. Bell; D. Copsey; C. Guiavarc'h; H. T. Hewitt; J. Ridley; M. J. Roberts (Geoscientific Model Development)
The early spinup of the HadGEM3 coupled model displays large-scale biases in the Southern Ocean at an eddy-permitting ocean resolution: the subpolar gyres and Antarctic Slope Current (ASC) are too active, the Antarctic Circumpolar Current (ACC) transport is too weak, and there are large-scale water mass biases on the Antarctic shelf and in the open ocean. Most of the biases persist for at least 100 years of the model spinup. This set of biases is largely absent with a non-eddying ocean model and reduced with an eddy-rich ocean model. We show that damping the gyres and the ASC in the eddy-permitting model, either by introducing a parameterization of baroclinic instability or by changing the lateral momentum boundary condition to increase bathymetric drag, acts to alleviate all the biases. This suggests that the fundamental issue in the eddy-permitting model may be to do with unresolved eddy processes and/or the representation of bathymetric drag on the flow. We investigate the structure of the biases in more detail and show that the eddy-permitting model has steep isopycnals near the Antarctic shelf slope, consistently with a strong ASC and reduced transport of Circumpolar Deep Water (CDW) onto the shelf. However, across the region of the ACC jets, the eddy-permitting model has shallower isopycnal slopes than the other models, consistently with a weaker ACC transport and warm near-surface biases in the open ocean.